Angioscopic Findings of Stenosis Versus Occlusion in Femoropopliteal Artery Disease. (April 2023) - Tashiro, Kazuma; Mori, Hiroyoshi; Tezuka, Takahiro; Omura, Ayumu; Wada, Daisuke; Sone, Hiromoto; Takei, Yosuke; Sasai, Masahiro; Sato, Tokutada; Suzuki, Hiroshi
Background: Despite the increase in the number of patients with peripheral artery disease (PAD), the pathophysiology is not fully elucidated. Recently, angioscopy with a 0.48-megapixel equivalent resolution camera became available for patients with PAD. We aimed to compare the plaque component between native stenosis and occlusion in the femoropopliteal artery using this modality. Materials and Methods: Thirty-two consecutive patients who underwent endovascular treatment for native femoropopliteal artery disease with angioscopy were studied. The major angioscopic classifications of each lesion were defined as follows: atheromatous plaque (AP) was defined as luminal narrowing without any protrusion, calcified nodule (CN) was defined as a protruding bump with surface irregularity, a mainly reddish thrombus was defined as organizing thrombus (OG), and organized thrombus (OD) was defined by more than half of the thrombus showing a whitish intima-like appearance. Results: A total of 34 lesions (stenosis, n=18; occlusion, n=16) from 32 patients were included. All stenotic lesions showed AP or CN (n=8 [44%], n=10 [56%], respectively), whereas all occluded lesions showed OG or OD (n=5 [31%], n=11 [69%], respectively), which amounted to a statistically significant difference (p<0.001). In occluded lesions, stiff wires (>3 g) were required to cross all lesions classified as OD, whereas this was not always necessary for lesions classified as OG (11 [100%] of 11, 1 [25%] of 5, respectively; p=0.04). Yellow color plaques were observed to a similar degree in all angioscopic classifications. Major adverse limb events, defined as amputation and any reintervention at 12 months, were highly variable, depending on the angioscopic findings, and tended to be more frequently observed in CN and OD (13% in AP, 40% in CN, 0% in OT, and 36% in OD, p=0.25). Conclusion: Angioscopy revealed varying components in stenosis and occlusion with different degrees of clinical impact. This may provide new information on the pathophysiology of PAD.